COMPARATIVE ANALYSIS OF BIOCHEMICAL MONITORING OF THE FUNCTIONAL STATE OF PROFESSIONAL ATHLETES AND THOSE WORKING AT ENTERPRISES OF A CONTINUOUS PRODUCTION CYCLE - Yashina E.R. ,; Kovalev S.P. ,; Turzin P.S. ,; Lukichev K.E. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to form the biochemical status of the body of professional athletes (hockey) based on a comparative assessment of indicators with a group of workers employed in production. Methods and structure of the study. A clinical examination of the team of hockey players was carried out using the generally accepted complex of clinical laboratory diagnostics for athletes (20 biochemical parameters) characterizing the activity of the main functional systems of the body of athletes and a similar study was performed on 30 men of comparable age working with the use of physical labor at a continuous cycle enterprise. Results and conclusions. The most significant biochemical indicators were identified, the values of which in the examined hockey players and workers had significant differences and deviations from physiological norms. An approximate form of the biochemical "profile" is proposed and the parameters are determined to determine the current state of the athlete. Recommendations have been developed to optimize the biochemical status of the body of athletes and workers, including the use of diets and specialized sports nutrition to prevent overtraining in athletes and overwork in workers using physical labor, and, consequently, reducing the likelihood of injuries and being on the list of injured athletes and the list. temporary disability of workers in production.